A comparative study on soot particle size distributions in premixed flames of RP-3 jet fuel and its surrogates. (1st January 2020) - Liu, Wang; Liang, Xin; Lin, Baiyang; Lin, He; Huang, Zhen; Han, Dong
Abstract: Soot particle size distribution functions (PSDFs) of RP-3 jet fuel and its three surrogates, n-decane and two n-decane/1, 2, 4-trimethylbenzene blends were studied on the burner stabilized stagnation flame platform. The PSDFs of all the flames showed transitions from the unimodal (nucleation mode only) to the bimodal (nucleation and accumulation modes) distribution as the separation distance increased. However, the surrogates did not well capture soot behaviors of RP-3 jet fuel. At most heights, the flame of the surrogate blend of higher 1, 2, 4-trimethylbenzene fraction showed the strongest nucleation and accumulation strengths, whereas the flame of RP-3 jet fuel had the lowest nucleation strengths and n-decane had the lowest accumulation strengths, respectively. Besides, the PSDF of the surrogate blend of higher 1, 2, 4-trimethylbenzene fraction showed later shifts from the nucleation mode to the accumulation mode and higher particle growth rates than the other flames. The PSDF of the n-decane flame shifted, at an earlier time, from the nucleation mode to the accumulation mode and showed lower particle growth rates. RP-3 jet fuel showed intermediate mobility diameters of the trough and median mobility diameters at the accumulation mode. The computed acetylene and benzene concentration profiles of the blend of higher 1, 2, 4-trimethylbenzene fraction were higher, suggesting its stronger nucleation strengths and faster particle growth rates, agreeing well with the experimental observation. On the other hand, RP-3 jet fuel produced larger number density of particles firstly and then lower number density than the other fuels with increased heights.